Human alveolar progenitors generate dual lineage bronchioalveolar organoids - Karen Hoffmann; Benedikt Obermayer; Katja Hönzke; Diana Fatykhova; Zeynep Demir; Anna Löwa; Luiz Gustavo Teixeira Alves; Emanuel Wyler; Elena Lopez-Rodriguez; Maren Mieth; Morris Baumgardt; Judith Hoppe; et al. (Communications Biology, 2022)
The GSK3 inhibitor CHIR99021 is required to maintain the alveolar lineage in alveolar progenitors grown in airway media or AT2 cells become plastic, with the observed effects acting outside of its role as a GSK3B inhibitor.